Kelulut (Trigona spp) Cultivation to Increase Production and Additional Income of Mangrove Ecotourism Peduli Pesisir Farmer Groups, Beras Basah Village, Pangkalan Susu Sub-District, North Sumatra, Indonesia - Basyuni, Mohammad; Mubaraq, Alfian; Aznawi, Andi Aznan; Sivaipram, Itchika; Amir, Ahmad Aldrie; Jumilawaty, Erni; Leopardas, Venus; Slamet, Bejo; Nuryawan, Arif; Siregar, Etti Sartina; Sulistyono, Nurdin (Journal of Community Services: Sustainability and Empowerment, 2024)
The cultivation of Kelulut (Trigona) honey bees has been initiated by the Peduli Pesisir Farmers Group (Mitra) in a mangrove-based agro-tourism area in Beras Basah Village, Pangkalan Susu District, North Sumatra. However, due to limitations in mastering the science and technology (IPTEKS) of kelulut cultivation and the number of stock owned by partners as well as several other aspects, partners have not been able to meet consumer demand, based on Focus Group Discussions (FGD) and community service team discussions with several group members. from informal farming and document searches, it can be seen that the partner has the right to manage an area of 4 hectares and it has great potential to increase the honey production of kelulut bees, because in this area there are various plants that produce flowers as a source of nectar/main food for kelulut bees. Based on some of the information above, a problem analysis was carried out by the community service team involving partners, so that an agreement was born to carry out several activities that could support the smooth transfer of science and technology, such as; counseling, discussions, training and the addition of a number of stup (kelulut bees + media).